VOLLEY BALL PASSING LEARNING MODEL FOR STUDENTS AGE 11-12 YEARS - Aida Fitriani; Widiastuti; Hernawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to produce a product of Learning Passing Learning Model Age 11-12 Years in Elementary School. The learning model is expected to help teachers during the physical education learning process, especially in volleyball. This study uses the ADDIE method. The results of the study resulted in a product in the form of a Passing Learning Model for the Age of 11-12 Years which had been validated and revised by 22 experts. Data were collected through documentation, interviews, and observations. Data analysis was done descriptively. The results of the study were in the form of a Passing Learning Model book for 11-12 Years Old. Based on the results of the study, it was proven that the Passing Learning Model for the Age of 11-12 Years could be developed and applied in volleyball learning in elementary schools. The Passing Learning Model of 11-12 years old can make a positive contribution in supporting the achievement of goals in physical education learning in elementary schools, because besides being able to improve volleyball under-passing skills, students can be motivated to do a variety of learning